2008
DOI: 10.1007/s00125-007-0915-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of elevated casual blood glucose level with coronary heart disease, cardiovascular disease and all-cause mortality in a representative sample of the Japanese population. NIPPON DATA80

Abstract: Aims/hypothesis High fasting blood glucose is one of the well-known risk factors for CHD. However, in certain settings, patients cannot always be expected to fast. For example, community screenings for cardiovascular disease (CVD) risk factors in Japan are performed under non-fasting conditions to achieve high participation rates. Thus, we examined a representative cohort of the Japanese population (n=9,444, follow-up period 17.3 years) to clarify whether high casual blood glucose (CBG) can predict CVD mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 38 publications
3
48
0
8
Order By: Relevance
“…The NIPPON DATA 80 Study indicated that DM, defined by nonfasting blood glucose levels, was a risk factor for CVD mortality. 33 In the Funagata Diabetes Study, IFG was not a risk factor Abbreviations: DM, diabetes mellitus; IFG, impaired fasting glucose. Multivariate analyses were adjusted for age, body mass index, hypertension, hyperlipidemia and smoking and drinking status.…”
Section: Discussionmentioning
confidence: 99%
“…The NIPPON DATA 80 Study indicated that DM, defined by nonfasting blood glucose levels, was a risk factor for CVD mortality. 33 In the Funagata Diabetes Study, IFG was not a risk factor Abbreviations: DM, diabetes mellitus; IFG, impaired fasting glucose. Multivariate analyses were adjusted for age, body mass index, hypertension, hyperlipidemia and smoking and drinking status.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline surveys were performed in 1980 (NIPPON DATA80) [13][14][15][16][17][18] and in 1990. [19][20][21] Detailed methods of NIPPON DATA have been described previously.…”
Section: Participants and Follow-upmentioning
confidence: 99%
“…Blood glucose levels were measured using the cupric-neocuproine method, and the values were adjusted by using the formula ((0.047 Â (glucose concentration in mg per 100 ml))À0.541) to obtain the approximate value measured by the hexokinase method, which gives levels in mmol l À1 . 18 Diabetes was defined as casual blood glucose level of 11.1 mmol l À1 or self-reported diabetes. 18 Serum albumin and total cholesterol levels were measured by a sequential autoanalyzer (SMA12/60; Technicon, Tarrytown, NY, USA) using bromocresol-green staining for albumin and the Lieberman-Burchard direct method for total cholesterol at a specific laboratory (presently the Osaka Medical Center for Health Science and Promotion).…”
Section: Biochemical and Physical Examinationsmentioning
confidence: 99%
See 2 more Smart Citations